One-year pivotal trial outcomes of the Nellix system for endovascular aneurysm sealing - Carpenter, Jeffrey P.; Böckler, Dittmar (Journal of vascular surgery, 2017)
Objective The Nellix EndoVascular Aneurysm Sealing (EVAS) System (Endologix, Inc, Irvine, Calif) is a novel approach to abdominal aortic aneurysm (AAA) treatment whereby polymer is used to fill the AAA sac. We report 1-year results of the investigational device exemption pivotal trial.Methods Eligible patients were treated at 30 sites in the United States and Europe. Inclusion criteria required an asymptomatic infrarenal AAA, with a neck length ≥10 mm and ≤60° angle, iliac artery blood lumen diameter 9 to 35 mm, access artery diameter ≥6 mm, and serum creatinine ≤2 mg/dL. Follow-up included computed tomography angiography scans at 30 days, 6 months, and 1 year that were evaluated by a core laboratory. The primary safety end point was 30-day major adverse events (MAEs), which were compared with a performance goal of <56% (the Society for Vascular Surgery open repair control group rate). The primary effectiveness end point was treatment success at 1 year, which was compared with a performance goal of >80%. Treatment success required procedural technical success and absence of AAA rupture during follow-up, conversion to open surgical repair, endoleak (type I or III) at 1 year, migration >10 mm causing complications or requiring secondary intervention, aneurysm enlargement, or secondary procedures through 1 year for resolution of endoleak, device obstruction or occlusion, or device defect.Results Of 150 treated patients, 149 (99.3%) completed 1-year follow-up. The MAEs rate at 30 days was 2.7% (95% confidence interval, 0.7%-6.7%), satisfying the primary safety end point (<56%). The 1-year treatment success was 94% (95% confidence interval, 88.6%-97.4%), achieving the primary effectiveness end point (>80%). At 1 year, key secondary outcomes included 6.7% MAEs, 4.7% serious device-related events, 1.3% AAA-related mortality, 3.7% secondary interventions, and 0.7% surgical conversions. MAEs through 1 year included death (n = 6), stroke (n = 3), bowel ischemia (n = 2), renal failure (n = 2), respiratory failure (n = 2), and myocardial infarction (n =1). One iatrogenic AAA rupture occurred and one AAA rupture was reported during follow-up. AAA sac enlargement (>5 mm) was 1.5% at 1 year. Endoleaks were present in four patients (3.1%) at 1 year (1 type Ib and 3 type II). Migration >10 mm occurred in three patients (2.3%), but none required secondary intervention. Conclusions Outcomes with this novel endovascular therapy for AAA, the Nellix EVAS System, are encouraging. The primary safety and effectiveness end points have been met. Low morbidity, low mortality, and high procedural and treatment success were achieved despite the inevitability of a learning curve and unique risks associated with a new device and technique. Long-term follow-up is in progress.